Solubility of Cyproterone Derivatives in the Presence of Hydroxypropyl-ß- Cyclodextrin: Experimental and Molecular Modeling Studies: Effect of hydroxypropyl--cyclodextrin on solubility of cyproterone derivatives - Zahra Rezaei; Soghra Khabnadideh; Mohammad Mehdi Zarshenas; Andia Khalili; Mohammad Reza Jafari (Iranian Journal of Pharmaceutical Sciences, 2010)
This study presents the influence of hydroxypropyl-ß-cyclodextrin (HPBCD) on the aqueous solubility of acyl esters of cyproterone. First, a number of esters of cyproterone were synthesized. Then the phase solubility analysis of the compounds in the presence of HPBCD was investigated in phosphate buffer solution at a pH of 7.4. To gain a better understanding of the complexation mechanism, the synthesized compounds were docked inside the HPBCD cavity using the Autodock program. The results show that the interaction between the synthesized compounds and HPBCD is of type AL and all of the compounds exhibited higher solubility as a result of complexation with HPBCD. The extent of increase in solubility was consistently greater as the ester chain length ascends by 4 carbon atoms. This increase in solubility is in agreement with the results obtained by calculating docking scores.